Barbados has a sweet idea [power generation from sugarcane breeding]. - Moore, S.K.
West Indies Central Sugar Cane Breeding Station has developed a breed of sugar cane especially suited to fuel electric power plants. Although fuel cane's sugar content and quality are lower, they're good enough to convert to ethanol, a product blended with gasoline to reduce its cost and replace harmful antiknock additives. In addition, fuel cane can grow during the regular cane's off-season, ensuring a year-round supply. With this sugarcane, the electric utility and the sugar industry in Barbados are negotiating a plan to replace up to 30 megawatts of the island's oil-fueled power generation.
Keywords: Indies Central Sugar Cane Breeding Station development; Electric power plants; Electric utility; Oil-fueled power generation; Power generation; Sugar industry